Towards an Adaptive Student Management Model: Insights from Residential Islamic Education - Ibnu Hajar; Abdurrahman Abdurrahman; Amiruddin Siahaan; Emelia Lubis (JURNAL AL-TANZIM, 2026)
This study aims to analyze student management in Islamic boarding schools through a multisite study to obtain a comprehensive understanding of student management practices. A qualitative approach with a multisite study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using cross-site analysis techniques. The findings reveal that student management is implemented through an integrated twenty-four-hour residential guidance system that emphasizes character development, discipline, strengthening religious practices, and a balanced integration of religious and formal education. Student management encompasses planning, orientation and adaptation, guidance, supervision, student services, administrative management, and continuous evaluation of student development, thereby supporting a holistic educational process. These findings demonstrate that student management extends beyond dormitory administration and functions as a comprehensive educational system that promotes students' academic, spiritual, and personal development. The study underscores the need to develop an adaptive, measurable, and value-based student management model to serve as a reference for strengthening student development systems in Islamic boarding schools across diverse educational contexts.